Experimental study of hydrogen trapping by carbides in low alloyed steels using Atom Probe Tomography - Moritz, Ludwig (My University, 2024)
Hydrogen embrittlement (HE) of high-strength low-alloy (HSLA) steels is a big problem. Several options are known to prevent/delay the embrittlement of the steels. One option is to trap the hydrogen at or inside the carbides. This could be interpreted as an energetic interaction, as the nano-sized carbides contribute to the mechanical strength of the material. This work investigates three different low alloyed steels, named in the thesis Steel-1, Ti-steel and V-steel. For the electrochemical D loading process, a 0.1M NaOH in D2O is used. The specimens are transferred at room temperature (RT) to the atom probe (AP). Crystallographic calibration was carried out for all measurements. For Steel-1 in the quenched state, no trapping can be seen. For the annealed specimens, the trapping capability can be argued. The Ti- and V-steel show D trapping. Besides the standard measurement, a room temperature degassing experiment was carried out for the Ti- and V-steel to get a qualitative insight into the strength of the traps.
Keywords: Atom Probe Tomography, Hydrogen Embrittlement, High-strength lowalloy steel, Hydrogen traps, Carbides